The drebrin/EB3 pathway regulates cytoskeletal dynamics to drive neuritogenesis in embryonic cortical neurons. Issue 2 (20th September 2021) - Poobalasingam, Thanushiyan; Bianco, Francesca; Oozeer, Fazal; Gordon‐Weeks, Phillip R.
Abstract: Co‐ordinating the dynamic behaviour of actin filaments (F‐actin) and microtubules in filopodia is an important underlying process in neuritogenesis, but the molecular pathways involved are ill‐defined. The drebrin/end‐binding protein 3 (EB3) pathway is a candidate pathway for linking F‐actin to microtubules in filopodia. Drebrin binds F‐actin and, simultaneously, the microtubule‐binding protein EB3 when bound to microtubule plus‐ends. We assessed the effect on neuritogenesis of gain‐ or loss‐of‐function of proteins in the drebrin/EB3 pathway in rat embryonic cortical neurons in culture. Loss‐of‐function of drebrin by gene editing or pharmacological inhibition of drebrin binding to F‐actin reduced the number of dynamic microtubules in the cell periphery and simultaneously delayed the initiation of neuritogenesis, whereas over‐expression of drebrin induced supernumerary neurites. Similarly, loss of EB3 inhibited neuritogenesis, whereas loss of end‐binding protein 1 (EB1), a related protein that does not bind to drebrin, did not affect neuritogenesis. Over‐expression of EB3, but not EB1, induced supernumerary neurites. We discovered that EB3 is more proximally located at dynamic microtubule plus‐ends than EB1 in growth cone filopodia allowing for continuous microtubule elongation as the drebrin/EB3 pathway zippers microtubules to F‐actin in filopodia. Finally, we showed that preventing the entry of dynamic microtubules into filopodia using a pharmacological inhibitor of microtubule dynamics is associated with a loss of EB3, but not EB1, from microtubule plus‐ends and a concurrent attenuation of neuritogenesis. Collectively, these findings support the idea that neuritogenesis depends on microtubule/F‐actin zippering in filopodia orchestrated by the drebrin/EB3 pathway. Abstract : We proposed that an intracellular pathway comprising the actin‐filament binding protein drebrin and the microtubule +TIP protein EB3 plays a role in coupling dynamic microtubules to actin filaments in filopodia that underlies neuritogenesis. Using genetic and pharmacological tools we tested experimentally the role of the pathway in cultures of embryonic cortical neurons. Our findings suggest a mechanism that cross‐links actin filaments in filopodia to growing microtubules by an interaction between drebrin, bound to actin filaments, and EB3 located at the microtubule growing tip. Proximo‐distal iteration of this cross‐linking would produce a zippering of growing microtubules to actin filaments supporting neuritogenesis.